Pengaruh Live Video Streaming Tiktok, Potongan Harga, dan Gratis Ongkir Terhadap Keputusan Pembelian - Febriah, Intan; Febriyantoro, Mohamad Trio (LPPM Universitas BSI, 2023)
This research is motivated by the trend of Tiktok during the COVID-19 pandemic. This trend can be used to overcome economic problems due to declining public purchasing power. The purpose of this study was to determine the effect of live video streaming on Tiktok, discounted prices, and free shipping on online purchasing decisions. The population of this study is Skintific product users in DKI Jakarta who buy products on the Tiktok live platform. The sampling method used was purposive sampling. The samples obtained were 114 respondents. Based on the results of this study it was found that Tiktok live video streaming and free shipping have a positive and significant effect on purchasing decisions. Meanwhile, price discounts have no effect on purchasing decisions. The results of this study can be used by related sellers as a consideration for increasing sales through increasing consumer purchasing decisions.Keyword: discounted prices, free shipping, purchasing decisions, Tiktok live video streaming